Evaluation of the contribution of values clarification to a brief mindfulness meditation intervention for anxiety. Issue 9 (15th March 2018) - Berghoff, Christopher R.; Forsyth, John P.; Ritzert, Timothy R.; Eifert, Georg H.; Anderson, Drew A.
Abstract: Objective: Evaluate the incremental effects of a computerized values clarification (VC) activity on anxiety symptomology and quality of life over and above establishment of a mindfulness meditation (MM) practice. Method: Anxious participants ( N = 120, Female = 86; M age = 22.26) were randomly assigned to a 2‐week, 10‐min daily MM practice + control task or a 2‐week, 10‐min daily MM practice + VC task. Pre‐assessments and post‐assessments included well‐established and ideographic self‐report measures. Results: Overall decreases in past week and past 24‐h anxiety symptom frequency, as well as increased quality of life during the previous 24‐h cycle only. VC did not have a demonstrable impact on outcomes. Conclusions: Though findings are preliminary, brief VC exercises may not enhance outcomes that follow from mindfulness practice. Additional research is needed to isolate specific and shared impacts of mindfulness‐based and values‐based treatment strategies on anxiety symptoms and quality of life.